Irisin counteracts high glucose and fatty acid-induced cytotoxicity by preserving the AMPK-insulin receptor signaling axis in C2C12 myoblasts - Naohiro Yano; Ling Zhang; Dennis Wei; Patrycja M. Dubielecka; Wei Lei; Shougang Zhuang; Ping Zhu; Gangjian Qin; Paul Y. Liu; Y. Eugene Chin; Ting C. Zhao (2020)
Irisin, a newly identified myokine, is critical to modulating body metabolism and biological homeostasis. However, whether irisin protects the skeletal muscles against metabolic stresses remains unknown. In this study, we determine the effect of irisin on high glucose and fatty acid-induced damages using irisin-overexpressed mouse C2C12 (irisin-C2C12) myoblasts and skeletal muscle from irisin-injected mice. Compared with empty vector-transfected control C2C12 cells, irisin overexpression resulted in a marked increase in cell viability and decrease in apoptosis under high-glucose stress. Progression of the cell cycle into the G2/M phase in the proliferative condition was also observed with irisin overexpression. Furthermore, glucose uptake, glycogen accumulation, and phosphorylation of AMPKα/insulin receptor (IR) β-subunit/Erk1/2 in response to insulin stimulation were enhanced by irisin overexpression. In irisin-C2C12 myoblasts, these responses of phosphorylation were preserved under palmitate treatment, which induced insulin resistance in the control cells. These effects of irisin were reversed by inhibiting AMPK with compound C. In addition, high glucose-induced suppression of the mitochondrial membrane potential was also prevented by irisin. Moreover, suppression of IR in irisin-C2C12 myoblasts by cotransfection of shRNA against IR also mitigated the effects of irisin while not affecting AMPKα phosphorylation. As an in vivo study, soleus muscles from irisin-injected mice showed elevated phosphorylation of AMPKα and Erk1/2 and glycogen contents. Our results indicate that irisin counteracts the stresses generated by high glucose and fatty acid levels and irisin overexpression serves as a novel approach to elicit cellular protection. Furthermore, AMPK activation is a crucial factor that regulates insulin action as a downstream target.